Effect of Fluid Bolus Therapy on Extravascular Lung Water Measured by Lung Ultrasound in Children With a Presumptive Clinical Diagnosis of Sepsis. (29th October 2018) - Long, Elliot; O'Brien, Adam; Duke, Trevor; Oakley, Ed; Babl, Franz E.; ,
Abstract : Objectives: Fluid bolus therapy for the treatment of sepsis may lead to the accumulation of extravascular lung water (EVLW) and result in respiratory dysfunction. We aimed to assess changes in EVLW using lung ultrasound (US) in children with a presumptive clinical diagnosis of sepsis after fluid bolus therapy and correlate these changes with respiratory signs. Methods: This work was a prospective observational study set in the emergency department of the Royal Children's Hospital. Children meeting international consensus criteria for sepsis receiving fluid bolus therapy were included. Respiratory signs were recorded, and lung US examinations were performed immediately before, 5 minutes after, and 60 minutes after fluid bolus therapy. A pediatric emergency physician blinded to the participants' identities and timing of US calculated an EVLW score from lung US. Results—Fifty fluid boluses were recorded in 41 children. The lung US score (range, 0–8) increased over the study period: median, 1 (interquartile range, 0–2) before fluid bolus therapy, 1 (interquartile range, 0–3) 5 minutes after fluid bolus therapy, and 3 (interquartile range, 1–4) 60 minutes after fluid bolus therapy. Respiratory effort, but not the respiratory rate or the presence of rales, increased over the study period and was correlated with the lung US score (ρ = 0.33; P  = .02). Conclusions: Extravascular lung water as measured by lung US increased after fluid bolus therapy in septic children and was correlated with an increase in the respiratory distress score. The respiratory rate and the presence of rales did not change over the study period. The role of lung US for titrating fluid bolus therapy in sepsis warrants further investigation.